Numerical investigation of contact loads of unsynchronised, dry-running screw machines. Issue 1 (1st November 2022) - Aurich, D; Brümmer, A; Wittig, A; Stangier, D; Tillmann, W; Thomann, C-A; Wittrock, A; Debus, J
Abstract : Unsynchronised, dry-running screw machines have advantages compared to conventional oil-injected and synchronised, dry-running screw machines. Because of the absence of an additional timing gear and no injected lubricant, the effort for manufacturing and assembly can be reduced and lubricant residues in the process gas are avoided. In this design the female rotor torque resulting from the gas pressure is transferred directly to the male rotor by the contacting rotor surfaces. To investigate this contact, a two-dimensional boundary element method contact algorithm is developed to calculate the loads in terms of contact tractions and sliding velocities. The contact kinematics of the screw rotors and the non-constant curvature of the rotor surfaces are considered. The movement between the screw rotors is transformed into a relative coordinate system fixed on the male rotor. Furthermore, the influence of manufacturing tolerances to the occurring contact loads are investigated.